The neuroscience of dissociative amnesia and repressed memory: Premature conclusions and unanswered questions - Otgaar, Henry (Legal and criminological psychology, 2025)
Purpose A heated debate exists on whether traumatic memories can be dissociated or repressed. One way in which researchers have attempted to prove the existence of dissociative amnesia or repressed memory is to examine whether claims of amnesia for traumatic events are associated with specific neural markers. Methods Here, we will argue that such neuroscientific examinations do not tell us whether traumatic memories can be unconsciously repressed or dissociated from consciousness, respectively. Results We discuss neuroscientific studies on dissociative amnesia and repressed memory and show that there are no reliable biological markers for dissociative amnesia and that the alleged involved brain areas are heterogenous among studies. Furthermore, we will demonstrate that it is unclear whether these studies truly involved patients with dissociative amnesia and that alternative explanations of dissociative amnesia were often not ruled out (e.g. malingering, organic amnesia). Moreover, we will make the case that the discussed patients in the studies do not meet the DSM-5 criteria for dissociative amnesia. Conclusions Taken together, neuroscientific research into dissociative amnesia does not present a convincing case for a biological basis of the purported memory loss.